Poultry and cattle manure effects on sunflower performance, grain yield and selected soil properties in Limpopo Province, South Africa - Matome J. Mokgolo; Jestino Mzezewa; Jude J.O. Odhiambo (South African Journal of Science, 2019)
The application of organic manures as alternatives to reduce the use of mineral fertilisers is considered a good agricultural practice for smallholder farmers. However, the effect of organic manure on soil properties and crop yield depends upon its application rate and its chemical composition. A field experiment was carried out during the 2013/2014 and 2014/2015 seasons at the University of Venda experimental farm (Limpopo Province, South Africa) to determine the effect of three organic manures (cattle, poultry and their 1:1 combination, 20 t/ha) on sunflower (Helianthus annuus L.) performance, grain yield and selected soil properties under rainfed conditions. Poultry manure produced the highest final infiltration rate and cumulative infiltration followed by cattle manure, their combination and the control in that order. Total nitrogen, calcium, and zinc were significantly different between treatments in the first season while potassium, sodium, and zinc were significantly different in the second season. Manure combination and poultry manure produced the highest organic carbon and available phosphorus, respectively, in both seasons compared to other treatments. Organic manure application had a significant (p<0.05) effect on dry matter, plant height and stem girth at all growth stages in the second cropping season but only in the flower bud stage for both parameters in the first season. Manure application in the second season resulted in an increase in the grain yield compared to the first season, except after application of poultry manure whereafter the grain yield decreased significantly by 168% from the first cropping season. The application of organic manure had a significant effect on sunflower grain yield, dry matter, head dry matter, plant height and stem girth throughout all growing stages in the second cropping season with poultry manure producing the best values.